Nahdlatul Ulama in Defending Indonesian Independence: The Battle of November 10, 1945 - Sa'adah, Putri Lailatus; Syah, M. Kautsar Thariq; Nurcahaya, Yan; Samsudin, Samsudin; Sudana, Djojo Soekarjo (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study examines the Jihad Resolution issued by Nahdlatul Ulama (NU) in response to the threat of a return to colonialism after the Proclamation of Indonesian Independence, focusing on its contribution to the Battle of November 10, 1945 in Surabaya. The Jihad Resolution, issued on October 22, 1945, became an important point in the mobilization of the people to defend independence. This research aims to analyze the historical background, content, and impact of the Jihad Resolution on the dynamics of physical struggle and the strengthening of the spirit of religion-based nationalism. The method used is qualitative with a historical approach. Data was collected through literature studies, analyses of archival documents, and review of related literature, including speeches, ulama fatwas, and historical testimonies. The analysis was carried out in a descriptive-analytical manner to understand the relationship between the religious dimension and the nation's struggle strategy. The results of the study show that the Jihad Resolution provides religious legitimacy to fight against the colonizers, so that it is able to unite various elements of society, both civilian and military, in the battle to defend Surabaya. In addition, this resolution shows the integration between Islamic values and nationalism, making the struggle to defend independence part of religious obligations.